2000
DOI: 10.2174/1381612003401019
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Therapy of Superficial Bladder Cancer

Abstract: Transurethral resection (TUR) of the superficial transitional cell carcinoma (TCC) of the bladder is known to be insufficient in controlling the disease because of the unacceptable rates of recurrence, progression and ultimate cystectomy. Adjuvant intravesical chemo-and/or immunotherapy is administered in an effort to enhance the efficacy of surgery alone. The initial tumor stage and grade, the multifocality of this cancer and the history of previous recurrences remain the determinant factors in survival. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 61 publications
(184 reference statements)
2
12
0
1
Order By: Relevance
“…Several other studies showed that net benefit after 1 year of follow-up is 12% for patients treated with mitomycin C (MMC) compared to patients without adjuvant treatment [4,5]. However, intravesical chemotherapy had no impact on progression to MIBC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies showed that net benefit after 1 year of follow-up is 12% for patients treated with mitomycin C (MMC) compared to patients without adjuvant treatment [4,5]. However, intravesical chemotherapy had no impact on progression to MIBC.…”
Section: Introductionmentioning
confidence: 99%
“…PDT showed some encouraging results [9] as well as those obtained by De Stasi et al [10] with sequential BCG and EMDA/MMC and both increase recurrence-free time; anyway, like chemotherapy, they have no effect on progression. It has been reported that the combination of heat treatment and chemotherapy instillation offers anticancer advantages over chemotherapy instillation alone in preventing or delaying tumor recurrence or progression [4,5]. A clear synergistic effect of MMC and hyperthermia was demonstrated in four human bladder cancer cell lines [6]: the uptake of the drug by the malignant cells and the intracellular distribution are improved by an increased cellular permeability; furthermore, drug metabolism and reaction with DNA is increased and DNA repair is inhibited [7].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 70% to 80% of patients with bladder cancer initially present with superficial disease that does not invade the muscularis propria (3). Transurethral resection (TUR) is the primary treatment method for nonmuscle-invasive or "superficial" carcinoma, which consists of the surgical removal of tumor nodules from the bladder wall (4,5). However, there is a high rate of tumor recurrence and high chance of disease progression after TUR alone (6).…”
Section: Introductionmentioning
confidence: 99%
“…Although transurethral resection (TUR) of superficial bladder cancer initially controls the disease, 65% of superficial tumors will recur at 5 years (90% at 15 years) and 10-20% will progress to muscle invasion at 5 years [2]. In order to prevent the post-TUR recurrence and progression of superficial bladder cancer, adjuvant intravesical chemoimmunotherapy has been introduced into clinical practice the last two decades [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several cytotoxic and immune modifying regimens have been tested, but current treatment schemes are usually empirical and insufficient [3]. Therefore, numerous prospective clinical trials concerning adjuvant intravesical therapy are in progress.…”
Section: Introductionmentioning
confidence: 99%